2018
DOI: 10.3390/met8030167
|View full text |Cite
|
Sign up to set email alerts
|

Compound Formation and Microstructure of As-Cast High Entropy Aluminums

Abstract: The aim of this work is to study the microstructure of four high entropy alloys (HEAs) produced by large scale vacuum die casting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…1, the thermodynamic calculations of equilibrium phases as a function of temperature were calculated using Thermo-Calc software and TCAL5 database 43 . According to previous works 4446 , the use of this database in Al-based HEAs and CCAs shows a good agreement with the experimental results. It should be noted that calculations were made for homogeneous alloys and not considering impurities, casting defects or oxides formed during the casting process.…”
Section: Resultssupporting
confidence: 84%
“…1, the thermodynamic calculations of equilibrium phases as a function of temperature were calculated using Thermo-Calc software and TCAL5 database 43 . According to previous works 4446 , the use of this database in Al-based HEAs and CCAs shows a good agreement with the experimental results. It should be noted that calculations were made for homogeneous alloys and not considering impurities, casting defects or oxides formed during the casting process.…”
Section: Resultssupporting
confidence: 84%
“…Jia et al investigated the AlLiMgCaSi high-entropy alloys and they found that the density of these alloys were 1.46 to 1.70 g/cm 3 and the strength was higher than 450 MPa, especially, as the Al 15 .5 Si 0.5 alloy exhibited good plasticity ~45 and ~60%, which is much higher than most of the lightweight high-entropy alloys [26]. Sanchez et al investigated on the as-cast high-entropy aluminums, and they found these alloys showed high hardness than other lightweight alloys [27,28]. Figure 6 shows the area of lightweight high-entropy alloys in the Ashby diagram of strength vs. density for structural materials, which we found that the strength of lightweight high-entropy alloys was much higher and the density much lower than some ceramics such as the SiC, Al 3 N, etc.…”
Section: Other Lightweight High-entropy Alloy Systemsmentioning
confidence: 99%
“…As an inexpensive and lightweight semi-metal element, Si element is added to the aluminum alloy to improve the mechanical properties of the alloy [2,5,[25][26][27] . Since Mg and Si are liable to form a high melting point intermetallic compound, for traditional cast aluminum alloys, the Mg/Si ratio has always been strictly controlled variable [28,29] .…”
Section: Alloy Designmentioning
confidence: 99%